Orexin-A/Hypocretin-1 Controls the VTA-NAc Mesolimbic Pathway via Endocannabinoid-Mediated Disinhibition of Dopaminergic Neurons in Obese Mice - Tunisi, Lea; D'Angelo, Livia; Fernández-Rilo, Alba Clara; Forte, Nicola; Piscitelli, Fabiana; Imperatore, Roberta; de Girolamo, Paolo; Di Marzo, Vincenzo; Cristino, Luigia (Frontiers in Synaptic Neuroscience, 2021)
Disinhibition of orexin-A/hypocretin-1 (OX-A) release occurs to several output areas of the lateral hypothalamus (LH) in the brain of leptin knockout obese ob/ob mice. In this study, we have investigated whether a similar increase of OX-A release occurs to the ventral tegmental area (VTA), an orexinergic LH output area with functional effects on dopaminergic signaling at the mesolimbic circuit. By confocal and correlative light and electron microscopy (CLEM) morphological studies coupled to molecular, biochemical, and pharmacological approaches, we investigated OX-A-mediated dopaminergic signaling at the LH-VTA-nucleus accumbens (NAc) pathway in obese ob/ob mice compared to wild-type (wt) lean littermates. We found an elevation of OX-A trafficking and release to the VTA of ob/ob mice and consequent orexin receptor-1 (OX1R)-mediated over-activation of dopaminergic (DA) neurons via phospholipase C (PLC)/diacylglycerol lipase (DAGL-α)-induced biosynthesis of the endocannabinoid 2-arachidonoylglycerol (2-AG). In fact, by retrograde signaling to cannabinoid receptor type 1 (CB1R) at inhibitory inputs to DA neurons, 2-AG inhibited GABA release thus inducing an increase in DA concentration in the VTA and NAc of ob/ob mice. This effect was prevented by the OX1R antagonist SB-334867 (30 mg/Kg, i.p.), or the CB1R antagonist AM251 (10 mg/Kg, i.p.) and mimicked by OX-A injection (40 μg/Kg, i.p.) in wt lean mice. Enhanced DA signaling to the NAc in ob/ob mice, or in OX-A-injected wt mice, was accompanied by β-arrestin2-mediated desensitization of dopamine D2 receptor (D2R) in a manner prevented by SB-334867 or the D2R antagonist L741 (1.5 mg/Kg, i.p.). These results further support the role of OX-A signaling in the control of neuroadaptive responses, such as compulsive reward-seeking behavior or binge-like consumption of high palatable food, and suggest that aberrant OX-A trafficking to the DA neurons in the VTA of ob/ob mice influences the D2R response at NAc, a main target area of the mesolimbic pathway, via 2-AG/CB1-mediated retrograde signaling.